2005
DOI: 10.1158/0008-5472.can-05-0800
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of Smad4 in Mouse Epidermis Results in Failure of Hair Follicle Cycling and Formation of Skin Tumors

Abstract: Smad4 is the common mediator of transforming growth factor-B (TGF-B) superfamily signaling, which functions in diverse developmental processes in mammals. To study the role of Smad4 in skin development, a keratinocyte-specific null mutant of Smad4 (Smad4 co/co ;K5-Cre) was generated in mice using the Cre-loxP system. The Smad4-mutant mice exhibited progressive alopecia as a result of the mutant hair follicles failing to undergo programmed regression. Sonic hedgehog (Shh) was only detected in Smad4-mutant hair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
117
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(133 citation statements)
references
References 43 publications
12
117
3
1
Order By: Relevance
“…In mice, loss of Smad4 results in early embryonic lethality because of impaired extraembryonic membrane formation and decreased epiblast proliferation (Sirard et al, 1998;Yang et al, 1998), whereas Smad4 heterozygous mice developed gastric polyposis and cancer because of haploinsufficiency (Takaku et al, 1999;Xu et al, 2000). Using tissue-specific knockout of Smad4 (Yang et al, 2002), we, along with others, showed that Smad4 deficiency could cause tumor formation in mammary tissue (Li et al, 2003), skin (Yang et al, 2005;Qiao et al, 2006), liver , forestomach (Teng et al, 2006) and colon (Kim et al, 2006). A recent study revealed that loss of Smad4 alone does not initiate pancreatic cancer formation, although it accelerates tumor formation on activation of oncogenic signaling, such as Kras (Izeradjene et al, 2007).…”
Section: Introductionmentioning
confidence: 64%
“…In mice, loss of Smad4 results in early embryonic lethality because of impaired extraembryonic membrane formation and decreased epiblast proliferation (Sirard et al, 1998;Yang et al, 1998), whereas Smad4 heterozygous mice developed gastric polyposis and cancer because of haploinsufficiency (Takaku et al, 1999;Xu et al, 2000). Using tissue-specific knockout of Smad4 (Yang et al, 2002), we, along with others, showed that Smad4 deficiency could cause tumor formation in mammary tissue (Li et al, 2003), skin (Yang et al, 2005;Qiao et al, 2006), liver , forestomach (Teng et al, 2006) and colon (Kim et al, 2006). A recent study revealed that loss of Smad4 alone does not initiate pancreatic cancer formation, although it accelerates tumor formation on activation of oncogenic signaling, such as Kras (Izeradjene et al, 2007).…”
Section: Introductionmentioning
confidence: 64%
“…To clarify whether or not Ppm1a-deficient keratinocytes, but not other cell types, mainly accounted for the delayed re-epithelialization observed in Ppm1a Ϫ/Ϫ mice, we generated keratinocyte-specific Ppm1a mutant (K5-Cre;Ppm1a fl/fl ) mice by breeding Ppm1a fl/fl mice with K5-Cre transgenic mice (29,30). Dramatic reduction of Ppm1a was demonstrated in the isolated Ppm1a mutant primary keratinocytes (supplemental Fig.…”
Section: Deletion Of Ppm1a Led To Delayed Re-epithelialization Duringmentioning
confidence: 99%
“…19 Skin-specific disruption of Smad4 results in increased epidermal proliferation consequently leading to squamous cell carcinoma formation. 20,21 Antitumor activity of BMPs may also be regulated by extracellular BMP inhibitors: expression of the BMP antagonist gremlin increased in basal cell carcinomas, in which gremlin promotes and BMPs inhibit cell proliferation. 22 However, mechanisms and downstream targets that mediate tumor suppressor function of the BMP signaling pathway in skin remain to be explored.…”
mentioning
confidence: 99%